The Effect of Chemical and Mechanical Degradation on Surface Roughness, Topography, Gloss, and Polish Retention of Three Composites Polished with Five Polishing Systems - Fatemeh Farzaneh; Mahshid Mohammadi-bassir; Mohammad Bagher Rezvani; Fahimeh Dehestani Ardakani (Tehran University of Medical Sciences, 2021)
Objective: Finishing and polishing (F/P) of composites is a fundamental step influencing the clinical service of restorations. The aim of this study was to evaluate the effect of different F/P systems on surface roughness, gloss, and polish retention of composite resins. Materials and Methods: One-hundred and five disc-shaped specimens (4×4 mm) were made from nanofilled, microhybrid, and microfilled composites (n=35). The specimens were divided into five subgroups (n=7) for F/P with Sof-Lex (4-step), Shofu (4-step), Cosmedent (3-step), Diacomp Composite-Pro (2-step), and Opti1Step systems. The surface roughness values (Ra and Rz) were measured before and after pH-cycling and simulated toothbrushing. Surface topography was assessed by using a scanning electron microscope (SEM) at three magnifications. For assessment of surface gloss, 45 rectangular specimens (10×8×2 mm) were fabricated from three composites (n=15) and randomly allocated to five subgroups (n=3). Surface gloss was measured before and after aging. The mean values were calculated and analyzed by two-way ANOVA, Tukey, and t-test. Level of significance was set at 0.05.  Results:  The composite type had no significant effect on surface roughness (P>0.05); however, the type of F/P system significantly affected it (P<0.05). The pH-cycling and simulated toothbrushing had no significant effect on gloss or polish retention of the three composites (P>0.05). Conclusion: Type of F/P system had a greater effect on surface roughness and gloss of composite resins than the type of composite.